Impact of Urinary Incontinence on Quality-Of-Life among Females Receiving Pelvic Floor Muscles Strengthening Exercises for Urinary Incontinence - Arooj Fatima, Fareeha Amjad, Alishba Mustansar, Sajjid Mahmood, Waqas Latif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Among women urinary incontinence (UI) is the most familiar problem and complain of lower urinary symptoms in urinary incontinence has found between 15% and 55%. It is a symptom with a lot of influence on quality of life of women majorly in their community-based, confidential and sexual domains. Aim: To see the impact of urinary incontinence on quality of life among females receiving pelvic floor muscles strengthening exercises for urinary incontinence. Study design: Cross-sectional study. Methodology: Patients (n=165) females with urinary incontinence were enrolled. The effect of urine incontinence on female quality of life, as well as the effect of pelvic floor muscle strengthening exercises on urine incontinency. The study inquired about the respondents’ backgrounds, daily routines, and the impact of incontinence on their social relationships, as well as the effects of urine incontinence on emotional and mental health. All female volunteers who have been dealing with urine incontinence for a few months will be included in the study. Analysis of data was done by SPSS v.26. Results: They were having physiotherapy for urine incontinency and it had not affected their quality of life but shown a positive effect in their household, social and personal activities. When the standard scoring method of IIQ-7 questionnaire applied the results of 0=Not at all,1= slightly, 2= moderate, 3= greatly, total mean of 7 items was 2.60 and 85% out of 100 get recovered and their quality of life improved by physiotherapy. Conclusion: It was concluded that the females who were receiving pelvic floor muscles strengthening exercises had good quality of life and urinary incontinence had not affected their quality of life (IIQ-7 score = 2.60) and had good impact on their quality of life. Keywords: Urine Incontinency, Quality of Life, Physiotherapy and Pelvic Floor Muscles.